2013
DOI: 10.1186/1471-2407-13-414
|View full text |Cite
|
Sign up to set email alerts
|

U-CARE: Internet-based stepped care with interactive support and cognitive behavioral therapy for reduction of anxiety and depressive symptoms in cancer - a clinical trial protocol

Abstract: BackgroundApproximately 20–30% of patients with cancer experience a clinically relevant level of emotional distress in response to disease and treatment. This in itself is alarming but it is even more problematic because it is often difficult for physicians and nurses to identify cancer patients who experience clinically relevant levels of anxiety and depression symptoms. This can result in persistent distress and can cause human suffering as well as costs for individuals and to the community.MethodsApplying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…27 It aims to investigate the effects of Internet-based support and treatment on anxiety, depression, and HRQoL in patients with breast, colorectal, or prostate cancer reporting symptoms of anxiety and depression. AdultCan includes a NILS program for patients with symptoms of anxiety and depression, as described in the present article.…”
Section: Settingmentioning
confidence: 99%
“…27 It aims to investigate the effects of Internet-based support and treatment on anxiety, depression, and HRQoL in patients with breast, colorectal, or prostate cancer reporting symptoms of anxiety and depression. AdultCan includes a NILS program for patients with symptoms of anxiety and depression, as described in the present article.…”
Section: Settingmentioning
confidence: 99%
“…[27] This reflects the fast-growing number of studies that are conducted on the cost-effectiveness or cost-utility of psychosocial care. In addition, several protocol papers of currently ongoing studies were identified,[9454647484950] which will provide new evidence on the cost-effectiveness or cost-utility of psychosocial care in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Another important way in which self‐guided interventions can be applied is through so‐called “massive open online interventions” (MOOIS) (Mattsson et al., ). These are Internet interventions that are made open to the public worldwide.…”
Section: Self‐guided Internet Interventionsmentioning
confidence: 99%